2009
DOI: 10.2353/ajpath.2009.090053
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Matriptase Suppression Underlies Spint1 Mutation-Associated Ichthyosis and Postnatal Lethality

Abstract: Hepatocyte growth factor activator inhibitor-1 (HAI)-1 is an epithelial Kunitz-type transmembrane serine protease inhibitor that is encoded by the SPINT1 gene. HAI-1 displays potent inhibitory activity toward a large number of trypsin-like serine proteases. HAI-1 was recently shown to play an essential role in postnatal epithelial homeostasis. Thus, Spint1-deficient mice were found to display severe growth retardation and are unable to survive beyond postnatal day 16. The mice present histologically with overt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 45 publications
2
40
0
1
Order By: Relevance
“…6,7 In mouse skin, HAI-1/SPINT1 interacts with matriptase to play a central role in regulated keratinization of the epidermis. 8,9 The participation of HAI-1/SPINT1 in the maintenance of epidermal integrity in zebrafish was also demonstrated. 13 Even in neoplastic cells, short hairpin RNA knockdown of HAI-1/ SPINT1 induced epithelial to mesenchymal transition in certain human epithelial cancer cell lines with enhanced metastatic colonization capability.…”
mentioning
confidence: 96%
“…6,7 In mouse skin, HAI-1/SPINT1 interacts with matriptase to play a central role in regulated keratinization of the epidermis. 8,9 The participation of HAI-1/SPINT1 in the maintenance of epidermal integrity in zebrafish was also demonstrated. 13 Even in neoplastic cells, short hairpin RNA knockdown of HAI-1/ SPINT1 induced epithelial to mesenchymal transition in certain human epithelial cancer cell lines with enhanced metastatic colonization capability.…”
mentioning
confidence: 96%
“…PAR-2 is activated by serine proteases, such as trypsin, factor Xa, KLKs 4, 5, 6, and 14, and tryptase, as well as membrane-anchored trypsin-like serine proteases, such as matriptase, prostasin, TMPRSS2, hepsin, and human airway trypsin-like protease. 17,27,43e46 Considering the established role of HAI-1 as a regulator of transmembrane trypsin-like serine protease activities, 17,24 it is possible to speculate that HAI-1 is a key regulatory molecule that controls PAR-2 activity and, hence, is critical in maintaining epidermal integrity. The current study provided evidence for this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…17,27,30 The evidence suggested that the most important cognate protease of HAI-1 in keratinocytes is matriptase. 24 Therefore, we hypothesized that the activity of matriptase was enhanced because of insufficient HAI-1, which eventually led to PAR-2 activation in HAI KD HaCaT cells. To test this hypothesis, we examined cellular expression of matriptase and its activity in culture supernatants of HaCaT cells.…”
Section: Trypsin-like Protease Activity Increases In Hai-1 Kd Hacat Cmentioning
confidence: 99%
See 1 more Smart Citation
“…An in vivo functional link between these two membrane-bound serine proteases and the two Kunitz inhibitors has also been observed in several animal studies. In the mouse and/or zebra fish, epidermal, placental or embryonic defects associated with genetic ablation of HAI-1 or HAI-2 can be rescued by simultaneous deletion or suppression of matriptase or prostasin [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%